2008
DOI: 10.1198/106186008x287328
|View full text |Cite
|
Sign up to set email alerts
|

Fast Adaptive Penalized Splines

Abstract: This paper proposes a numerically simple routine for locally adaptive smoothing. The locally heterogeneous regression function is modelled as a penalized spline with a smoothly varying smoothing parameter modelled as another penalized spline. This is being formulated as hierarchical mixed model, with spline coefficients following a normal distribution, which by itself has a smooth structure over the variances. The modelling exercise is in line with Baladandayuthapani, Mallick & Carroll (2005) or Crainiceanu, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 28 publications
2
62
1
Order By: Relevance
“…Alternatively, a parametric bootstrap method can be used to estimate E y ðVarðbjyÞÞ by generating a set of bootstrap replicates y* from the empirical distribution b f ð yÞ according to model (1) with the parameters replaced by their estimates from the EM algorithm. ; which is the price of our Laplace approximation compared to a full Bayesian approach as previously noted (Krivobokova et al 2008;Skrondal and RabeHesketh 2009). Finally, the C.I.…”
Section: Detailed Derivation Of the Estimation In The Ace(t)-p Modelmentioning
confidence: 86%
See 1 more Smart Citation
“…Alternatively, a parametric bootstrap method can be used to estimate E y ðVarðbjyÞÞ by generating a set of bootstrap replicates y* from the empirical distribution b f ð yÞ according to model (1) with the parameters replaced by their estimates from the EM algorithm. ; which is the price of our Laplace approximation compared to a full Bayesian approach as previously noted (Krivobokova et al 2008;Skrondal and RabeHesketh 2009). Finally, the C.I.…”
Section: Detailed Derivation Of the Estimation In The Ace(t)-p Modelmentioning
confidence: 86%
“…Based on this strategy, Krivobokova proposed a unified EM-type iterative procedure (Krivobokova et al 2008) to estimate the spline coefficients and the penalizing coefficients (now transformed to the variances of random effects in the linear mixed model) simultaneously by estimating the spline coefficients through an iterated weighted least-squares (IWLS) algorithm and employing an approximation algorithm (Breslow and Clayton 1993) to iterate between the estimation of the spline coefficients and minimization of the marginal log-likelihood. More specifically, following the same spirit, the marginal likelihood in our case is whereK andL are the numbers of positive eigenvalues of D A and D C : By applying a Laplace approximation to the integrand of (4) with the condition of K; L ( n M þ n D ; we obtain the 22 loglikelihood…”
Section: Stable Estimation Of Variance Curves Using Penalized Splinesmentioning
confidence: 99%
“…A similar idea was suggested in a fully Bayesian framework with d = 1 and MCMC techniques by Crainiceanu et al (2007). To overcome the numerically intensive computations of the latter, Krivobokova et al (2008) suggested to use the Laplace approximation of the likelihood. They have shown, that the resulting estimator is nearly identical to the Bayesian one, but can be obtained with considerably smaller numerical effort.…”
Section: Simultaneous Bands For Additive Models With Spatially Heteromentioning
confidence: 99%
“…In this article we extend the flexible adaptive curve estimation of Krivobokova et al (2008) to account for heteroscedasticity in the data and the approach of Krivobokova et al (2010) to additive models in order to analyze the data on stunting by age in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…A heuristic approach would be to pick γ 2 such that some smoothing is obtained, but not too much. Another approach is to estimate the parameter, using AIC, GVC or REML methods, see [11,14].…”
Section: Dependence Testingmentioning
confidence: 99%